2002
DOI: 10.4049/jimmunol.169.1.359
|View full text |Cite
|
Sign up to set email alerts
|

The Murine Cytomegalovirus Immunomodulatory Gene m152 Prevents Recognition of Infected Cells by M45-Specific CTL But Does Not Alter the Immunodominance of the M45-Specific CD8 T Cell Response In Vivo

Abstract: Although in vitro studies have shown that herpesviruses, including murine CMV (MCMV), encode genes that interfere with the MHC class I pathway, their effects on the CTL response in vivo is unclear. We identified a Db-restricted CTL epitope from MCMV M45 by screening an MCMV genomic library using CTL clones isolated from mice infected with MCMV lacking m152. Because m152 severely inhibits CTL recognition of M45 in vitro, we questioned whether an M45-specific response would be generated in mice infected with wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 35 publications
7
97
0
Order By: Relevance
“…In concurrence with other reports (11,12,48,51), our results show that an effective CD8 T-cell response begins to develop at day 5 and peaks at day 7 following infection with MCMV. The studies presented here also demonstrate a significant reduction in the recruitment of activated antigen-specific CD8 T cells, as measured by the release of IFN-␥ upon restimulation with the MCMV M45 peptide, in CXCR3-deficient mice infected with MCMV for 5 or 7 days.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In concurrence with other reports (11,12,48,51), our results show that an effective CD8 T-cell response begins to develop at day 5 and peaks at day 7 following infection with MCMV. The studies presented here also demonstrate a significant reduction in the recruitment of activated antigen-specific CD8 T cells, as measured by the release of IFN-␥ upon restimulation with the MCMV M45 peptide, in CXCR3-deficient mice infected with MCMV for 5 or 7 days.…”
Section: Discussionsupporting
confidence: 80%
“…In order to quantitate CD8 T-cell responses specific to MCMV, flow cytometric analysis was used to determine the direct binding of the TCR with a class I tetrameric major histocompatibility complex of H-2D b and the immunodominant peptide from the M45 viral protein (11,12). To enumerate T cells, hepatic leukocytes were stained with CD8␣-FITC monoclonal antibody as described above and with the M45-HGIRNASFI-D b tetramer (12), followed by streptavidin-allophycocyanin or streptavidin-PE (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, detection of priming in the presence of virus-encoded mechanisms that impair direct presentation implicate a component of cross-priming in viral immunity (56,57). We observed in our study that under conditions that allow DC ample access to infected cells, all DC subsets could efficiently present viral Ags via MHC class I, independent of their constitutive crosspresentation capacity.…”
Section: Discussionsupporting
confidence: 49%
“…50 Studies in murine CMV have demonstrated that CD8 ϩ CTLs specific for the M45 antigen, which is not presented by cells infected with wild-type virus in vitro due to the m152 immune evasion protein, are elicited in vivo after infection with wild-type virus, and this has been suggested to occur by cross-presentation. 32 In preliminary studies, we found the human CMV-specific CTL clones isolated here able to recognize uninfected dendritic cells (DCs) that were cocultured with allogeneic AD169-infected fibroblasts (T.J.M. and S.R.R., unpublished data, February 2002).…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Studies of the specificity of the CD8 ϩ CTL response induced in mice by experimental inoculation with murine CMV identified CTL responses to CMV antigens that are not presented by cells infected with wild-type CMV due to viral interference with class I antigen presentation. [32][33][34][35] In humans, Elispot assays with synthetic peptides selected from 14 human CMV proteins identified in some donors a significant response to pp50 in addition to pp65 and IE-1, and a low frequency response to peptides from US2, US3, US6, US11, UL16, and UL18, which have not previously been identified as target antigens. 36 Therefore, it is conceivable that major CD8 ϩ CTL responses specific for CMV antigens may be present in vivo but have gone undetected using fibroblasts permissively infected with wild-type CMV or with vaccinia recombinant viruses encoding only a few selected CMV proteins as stimulator cells.…”
Section: Introductionmentioning
confidence: 99%